Kajian Bauran Promosi Di Perguruan Tinggi “X” - Alida Wahyuni (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
Marketing of higher education falls into the category of services marketing. For “X” School, to attract potential students requires special methods and strategy. The objectives of the study are to: 1) Review and analyze of promotion mix in its effort to promote the institution; 2) review and analyze the most effective promotional mix in its effort to promote the institution. The results showed that: 1) the School has implemented a promotional mix. There are 6 ways to do that: advertising, sales promotion, publicity and public relations, personal selling, word of mouth, direct mail and e-marketing. The six ways are carried out simultaneously; 2) The most effective promotional mix is personal selling. For three years (2007, 2010, and 2011) proved it the most effective method. For 2008, the most effective promotional mix is word of mouth, dan for 2009, the most effective promotional mix is sales promotion. The most effective promotional mix in “Very Strong” category is personal selling could affect 956 students.